HIV-Related Stigma Affects Cognition in Older Men Living With HIV. (1st February 2019) - Lam, Austin; Mayo, Nancy E.; Scott, Susan; Brouillette, Marie-Josée; Fellows, Lesley K.
Abstract : Background: Stigma remains a reality for many people living with HIV. Stigma bears on mental health, but we hypothesized that it might also affect cognition, in turn affecting function. Methods: We estimated the impact of HIV-related stigma on brain health and everyday functioning among 512 older white men living with HIV in Canada, using the International Classification of Functioning, Disability and Health as a comprehensive framework to integrate biopsychosocial perspectives. Experience of HIV-related stigma, as indicated by a single self-report item, was related to cognitive test performance, cognitive symptoms, and mood. Structural equation modeling was used to estimate the relationships between these variables. Findings: A comprehensive structural equation model was built including personal, environmental, and biological factors, measures of mental and cognitive health, activity limitations, and participation restrictions. HIV-related stigma contributed to lower cognitive test performance and worse mental health. These in turn affected real-world function. The paths from stigma to cognition and mood had distinct downstream effects on physical, cognitive, and meaningful activities. Interpretation: This provides evidence that HIV-related stigma is a threat to cognitive as well as mental health, with a negative impact on everyday function in men aging with HIV. This argues for direct links between the psychosocial and biological impacts of HIV at the level of the brain. Stigma reduction may be a novel route to addressing cognitive impairment in this population. Funding: Operating support was provided by the Canadian Institutes of Health Research (TCO-125272) and by the CIHR HIV Clinical Trials Network (CTN-273). Abstract : Supplemental Digital Content is Available in the Text.